Indigenous fishing method used for catching spiny eels (Macrognathus spp.) in floodplain wetlands of Assam, India - Bhattacharjya, B. K.; Saud, B. J.; Debnath, D.; Yadav, A. K.; Borah, Simanku (Journal of the Inland Fisheries Society of India, 2019)
The present paper describes ITK associated with a unique indigenous fishing method used to catch mud-dwelling spiny eels (Macrognathus spp.) in floodplain wetlands of Assam by Bhatiya community in Lower Assam (locally called Akra mara) as well as by the Mising tribe in Upper Assam (Germe-Kenane). Here the spiny eels are caught by piercing them with a swiftswinging motion of a curved pointed barbless iron hook with a long bamboo handle. The specialized fishing method and the ITK associated with it were studied in 25 villages located around 12 floodplain wetlands (beel/ pitoni) of the study area. In this paper, we discussed how the two communities made effective use of the narrow visual field of the spiny eels through their traditional wisdom to catch these bottom dwelling fishes, which are otherwise difficult to catch.Keywords Indigenous Technical Knowledge, Akra mara, Germe-Kenane, Bhatiya community, Mising tribe,Macrognathus spp., Floodplain wetland (beel), Assam